Effectiveness of Olympic Combat Sports on Balance, Fall Risk or Falls in Older Adults: A Systematic Review - Herrera-Valenzuela, T (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
This systematic review and meta-analysis aimed to assess the available body of published peer-reviewed articles related to the effects of Olympic combat sports (OCS), compared with ac-tive/passive controls, on balance, fall risk, or falls in older adults. The TESTEX and GRADE scales assessed the methodological quality and certainty of the evidence. The protocol was registered in PROSPERO (code: CRD42020204034). From 1496 records, eight studies were included, involving 322 older adults (64% female; mean age = 71.1 years). The TESTEX scale revealed all studies with a score ≥ 60% (moderate-high quality). The GRADE scale indicated all studies with at least some concerns, up to a high risk of bias (i.e., was rated very low). Meta-analyses were planned, although the reduced number of studies precluded its incorporation in the final manuscript. Only two from six studies that assessed balance found improvements after OCS compared to controls. No differences were found between OCS vs. control groups for fall risk or falls. The available evidence does not allow a definitive recommendation for or against OCS interventions as an effective strategy to improve balance and reduce the fall risk or falls in older adults. Therefore, more high-quality studies are required to draw definitive conclusions. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.